Metodyka identyfikowania kierunków restrukturyzacji w przedsiębiorstwach gospodarki publicznej - Mietlewski, Zygmunt; Walkowiak, Ryszard (Identification of trends of changes in companies of the public economy, 2005)
The change always means restructuring in the company. It is the purpose of restructuring moving resources from lower levels of productivity to higher ones. Restructuring is being united in Poland wrongly. The main reason is that it refers to people, who often loose their jobs because of restructuring. It means that people only in theory are the most valuable resource in company. It's wrong because people are the most valuable resource for the company in the contemporary economy. Authors are presenting in the report the authoring method of identifying trends of changes in the company which is involving the whole leadership into the process of changes (of restructuring). This process is highly humanized - oriented to people.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 297-304